2008
DOI: 10.1177/154405910808700405
|View full text |Cite
|
Sign up to set email alerts
|

An Anti-c-Fms Antibody Inhibits Orthodontic Tooth Movement

Abstract: Orthodontic force induces osteoclastogenesis in vivo. It has recently been reported that administration of an antibody against the macrophage-colony-stimulating factor (M-CSF) receptor c-Fms blocks osteoclastogenesis and bone erosion induced by tumor necrosis factor-alpha (TNF-alpha) administration. This study aimed to examine the effect of an anti-c-Fms antibody on mechanical loading-induced osteoclastogenesis and osteolysis in an orthodontic tooth movement model in mice. Using TNF receptor 1- and 2-deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 22 publications
3
61
1
1
Order By: Relevance
“…The anti-c-Fms antibody significantly inhibited orthodontic tooth movement, markedly reducing the number of osteoclasts in vivo. 2 These findings suggest that M-CSF plays an important role in mechanical loading-induced osteoclastogenesis and bone resorption during orthodontic tooth movement mediated by TNF-␣. Because root resorption is understood to be performed by odontoclasts, similarly to osteoclasts in bone resorption, we hypothesized that the anti-c-Fms antibody might inhibit odontoclastogenesis and root resorption during orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The anti-c-Fms antibody significantly inhibited orthodontic tooth movement, markedly reducing the number of osteoclasts in vivo. 2 These findings suggest that M-CSF plays an important role in mechanical loading-induced osteoclastogenesis and bone resorption during orthodontic tooth movement mediated by TNF-␣. Because root resorption is understood to be performed by odontoclasts, similarly to osteoclasts in bone resorption, we hypothesized that the anti-c-Fms antibody might inhibit odontoclastogenesis and root resorption during orthodontic tooth movement.…”
Section: Introductionmentioning
confidence: 77%
“…It has been reported recently that adminis-tration of an antibody against the M-CSF receptor c-Fms (anti-c-Fms antibody) blocked osteoclastogenesis and orthodontic tooth movement. 1,2 Root resorption often is observed as an undesirable side effect of orthodontic treatment. It is a very serious problem for most clinicians, but it is still not understood.…”
Section: Introductionmentioning
confidence: 99%
“…To further investigate the role of TNFRs, tooth movement experiments using double-mutated mice for both TNFR1 and TNFR2 were performed. The experiment showed significant decreases in the amount of tooth movement in the double-mutated mice [45]. These results suggested that TNF-α is associated with orthodontic tooth movement.…”
Section: Mechanical Force Loading-induced Osteoclast Formation and Bomentioning
confidence: 75%
“…Therefore, the mice tooth movement models can provide an understanding of the molecular mechanisms involved not only in tooth movement but also in mechanical loadinginduced bone remodeling. A nickel-titanium (Ni-Ti) coil spring to obtain a continuous force for tooth movement is suitable for exerting continuous orthodontic force in mice models [44,45]. The process of orthodontic tooth movement occurs by repeated alveolar bone resorption on the pressure side and bone formation on the tension side of teeth [46].…”
Section: Mechanical Force Loading-induced Osteoclast Formation and Bomentioning
confidence: 99%
“…Bacterial infection and lipopolysaccharide (LPS) are reported to induce osteoclast formation and inflammatory bone loss, as seen in periodontal diseases [40,41]. LPS is major component of bacteria and is reported to be an inducer of inflammation and pathological bone resorption.…”
Section: The Inhibitory Effect Of the Anti-c-fms Antibody In Pathologmentioning
confidence: 99%